The Influence of Leadership, Work Environment, Work Motivation on Work Discipline at PDAM Tirta Kamuning Kuningan District - Rahmat, Pupu Syaiful; Djuniardi, Dede; Prayudi, Deri; Surya, Apria Ade (International Journal Administration, Business & Organization, 2024)
The study aims to understand and analyze how leadership, work environment, and work motivation impact work discipline. This is a descriptive quantitative study aimed at examining influence among two or more variables. The variables in this research are leadership, work environment, and work motivation as independent variables, and work discipline as dependent variable. Data were analyzed using multiple linear regression analysis, t-tests, and F-tests. The result showed that leadership, work environment, and work motivation impact of work discipline by 73.6%. Leadership yield a positive and significant impact on work discipline, the work environment yield a positive and significant impact on work discipline, and work motivation yield a positive and significant impact on work discipline. In other words, the more effective the leadership, work environment, and work motivation, the higher the work discipline. Therefore, leadership, work environment, and work motivation need to be further improved in the future as these three factors can influence and enhance work discipline.